Study on Level of Awareness and Readiness of UTHM Students in Building Information Modeling (BIM) - Rahimee, Nur Atikah; MOHAMMAD SOFFI BIN MD NOH, (Recent Trends in Civil Engineering and Built Environment, 2021)
Building Information Modeling (BIM) is a new software technology that help the building industry to revolutionise into a digitised, informative model. In the construction industry, the use of BIM required higher budgets, skills and expertise for practitioners. The adaptation of BIM in the Malaysian construction industry is indicated to be inferior by previous research. The aim of this study is to assess the level of awareness of UTHM students in BIM and to analyse readiness of UTHM students in learning of BIM course. Data was collected using a self-completion online survey based on the structured questionnaire survey and data were obtained from 207 students. Descriptive statistics have been used to deduce total data and provide insights of a variety of collected data. The findings of the data analysis were carried out with the help of IBM SPSS software Statistics 26.0. The results indicated that students have heard about BIM but do not understand its concepts. It also indicated that the respondents were not prepared to work in a BIM enabled environment because their courses did not prepare them well.